Rethinking education and health in a post pandemic world / Farah Adilla Ab Rahman - Ab Rahman, Farah Adilla (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The COVID-19 pandemic has forced a reevaluation of essential aspects of travel, trade, and globalisation. With the closure of airspaces and the rise of video conferencing platforms like Zoom and Microsoft Teams as practical and cost-effective alternatives, daily life norms have undergone significant changes. Home offices have become standard for many, and education has shifted online across all levels, from primary schools to universities. This shift to online education is referred to as "Teleeducation." Similarly, the provision of healthcare services has increasingly moved online, a practice known as "Telehealth" (Field, 1996). Michel, Murugasampillay, Sauter, and Tanner (2022) stated that the pandemic provides an opportunity for higher education institutions to rethink their strategies and foster collaborations. These developments align with initiatives such as decolonizing global health and higher education, aiming for a more equitable and sustainable global educational system—Teleeducation.